Dynamic ownership and private benefits - Breugem, Matthijs; Corvino, Raffaele (Journal of Corporate Finance, 2021)
We quantify private benefits of control by estimating a structural model of optimal shareholding using data on the ownership dynamics of Italian public companies. In the model, shareholders must maintain a minimum stake in the company to extract control benefits, which leads to infrequent trading of large blocks, and which is consistent with the empirical evidence. We estimate that control benefits account for 2% (4%) of the market value of the equity (block), and controlling shareholders earn a sizeable premium from the block holding on top of the market value of the shares. Also, we provide evidence that large block ownership and ownership persistence are associated with higher stock returns.